Application of Social Cognitive Theory: Tertiary Prevention Behavior in Patients with Type 2 Diabetes Mellitus in Ponorogo Hospital, East Java, Indonesia - Nur Aida Yuliana; Pawito Pawito; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Diabetes Mellitus (DM) is a non-communicable disease that becomes a serious threat to global health. This disease is a serious chronic disease because it cannot be cured. An increasing number of cases of non-communicable diseases that are associated with risk factors are in line with lifestyle changes that increasingly modern. This study aimed to analyze the effect of the variables in Social Cognitive Theory on tertiary prevention behavior in patients with type 2 Diabetes Mellitus.Subjects and Method: This was a cross-sectional study design. This study was conducted on patients with type 2 DM in the hospital in Ponorogo Regency, East Java, from January to February 2020. There were 200 patients with type 2 DM as the sample of the study. The sample was taken by random sampling. The dependent variable was Tertiary prevention behavior of type 2 DM. The independent variables were observational learning, role model, vicarious experience, imitation, attitude, outcome expectations, knowledge, reinforcement, self-efficacy, and self-management. The data were collected through a set of questionnaires. The data were analyzed based on Path Analysis using stata 13 application.Results: Tertiary prevention behavior of type 2 DM was directly increased by strong imitation (b= 1.40; 95% CI= 0.51 to 2.28; p= 0.002), good knowledge (b= 1.36; 95% CI= 0.48 to 2.25; p= 0.002), positive attitude (b= 1.32; 95% CI= 0.44 to 2.19; p= 0.003), strong self-efficacy (b= 1.07; 95% CI= 0.18 to 1.96; p= 0.018), and good self-management (b= 2.26; 95% CI= 1.31 to 3.22; p <0.001). Tertiary prevention behavior of type 2 DM was indirectly affected by observational learning, role model, vicarious experience, outcome expectation, and reinforcement.Conclusion: Tertiary prevention behavior of type 2 DM is directly increased by strong imitation, good knowledge, positive attitude, strong self-efficacy, and good self-management. Tertiary prevention behavior of type 2 DM is indirectly affected by observational learning, role model, vicarious experience, outcome expectation, and reinforcement.Keywords: social cognitive theory, type 2 Diabetes Mellitus.Correspondence: Nur Aida Yuliana. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: Aidayuliana17@gmail.com.Mobile: +628-5790767582.Journal of Health Promotion and Behavior (2020), 5(1): 157-168https://doi.org/10.26911/thejhpb.2020.05.03.02